2022
DOI: 10.3390/pathogens11080868
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii in African Wildlife: A Systematic Review

Abstract: Toxoplasma gondii (T. gondii) is a protozoan parasite, which infects a wide variety of mammals and bird species globally. In large parts of the world, this parasite is relatively well documented in wildlife species, however, this topic is poorly documented in Africa. The current review systematically explores the presence and distribution of T. gondii in African wildlife species through a key word search in PubMed, Web of Science and CAB Direct. A total of 66 records were identified and included in the qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Toxoplasma gondii (Conoidasida, Sarcocystidae) is an apicomplexan protozoan that causes a zoonotic infection known as toxoplasmosis. This parasite is one of the most resilient and persistent living parasites, able to infect many endothermic vertebrates including humans [ 1 ]. The Food and Agriculture Organization of the United Nations (FAO) identified toxoplasmosis among the 10 most important foodborne diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasma gondii (Conoidasida, Sarcocystidae) is an apicomplexan protozoan that causes a zoonotic infection known as toxoplasmosis. This parasite is one of the most resilient and persistent living parasites, able to infect many endothermic vertebrates including humans [ 1 ]. The Food and Agriculture Organization of the United Nations (FAO) identified toxoplasmosis among the 10 most important foodborne diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations of T. gondii in carnivores in South Africa and neighboring countries have focused mainly on the detection of antibodies specific to T. gondii ( Bokaba et al., 2022 ; Omonijo et al., 2022 ). These studies have shown a significant circulation of the parasite in both wild and domestic environments, with expectedly a higher prevalence in carnivores than in herbivores ( Bokaba et al., 2022 ). However, qPCR-based results are particularly valuable in wildlife studies, as validated serological tests are often not available for the host species under study.…”
Section: Discussionmentioning
confidence: 99%